From cesspool to fortified paradise: Analyzing news media territorial assemblages of rehabilitating Boracay Island, Western Philippines - Canoy, Nico A (Archīum Ateneo, 2020)
Sustainability initiatives have expanded beyond the rehabilitation of physical environments towards the reconstruction of discourses that shape human-nature interactions. In the present study, the discursive-materiality of territorial assemblages of sustainability were examined by analyzing tabloid news report coverage of the closure, rehabilitation, and reopening of Boracay, an island in the Western Philippines hailed as one of the most popular beach destinations in Asia. News reports about Boracay from eight local tabloids (n = 507) were collected and analyzed in two phases. The data corpus underwent basic descriptive coding through a text mining strategy called Latent Dirichlet Allocation (LDA), a confirmatory form of analysis that grouped data into clusters of meaning. From these initial clusters, discursive-material assemblages and their respective elements were critically mapped and identified through further interpretative analysis. Throughout the process of rehabilitation, Boracay was (re)constructed from a cesspool into a fortified paradise. These discursive-material assemblages of sustainability are further discussed in relation to the broader political climate of the current administration, as well as, the reproduction of claiming territories of public good in online space.